(untitled) (Journal of the Bangladesh Agricultural University, 2017)
An investigation was carried out on the limnological aspects of Ashura beel at Dinajpur district in Bangladesh. Several limnological parameters were evaluated from March 2013 to October 2013 from three sampling sites namely Kajladoho, Burirdoho and Sonnasydoho. Physical, chemical and biological parameters were analyzed fortnightly both at the field level and departmental laboratory of Fisheries Management, Hajee Mohammad Danesh Science and Technology University, Dinajpur. Findings revealed that only water level in three sampling sites varied significantly. The ranges of water temperature, transparency, water level at three sampling sites were 24 to 35.50°C, 17 to 27.50 cm and 0.58 to 2.44 m, respectively. Moreover, the dissolved oxygen concentration, pH, total alkalinity, total hardness and phosphate-phosphorus concentration were also remained within optimum ranges. Thirty four genera were recorded where phytoplankton includes 29 genera belonging to four groups such as euglenophyceae, cyanophyceae, bacillariophyceae and chlorophyceae and five genera of zooplankton in the four groups namely copepoda, rotifera, cladocera and crustacean larvae. Phytoplankton was dominated by chlorophyceae and zooplankton dominated by copepoda. The abundance of phytoplankton was positively correlated with water temperature, water level, dissolved oxygen, alkalinity, hardness, pH, and phosphate-phosphorus. On the other hand, abundance of zooplankton negatively correlated with water temperature, transparency and water level. However, from the findings of this study suggested that the water quality parameters of the selected sites were found to be suitable for the survival of aquatic organism. J. Bangladesh Agril. Univ. 15(1): 103-112, January 2017